Evaluation of the correlation between SPAD readings and absolute chlorophyll content of maize under different nitrogen supply conditions - Simkó, Attila; Veres, Szilvia (Acta Agraria Debreceniensis, 2019)
Currently, one of the most important objectives of agriculture is to maintain the principles of the sustainability. The use of precision technologies in agriculture belongs to this topic. The use of precision technologies is increasingly widespread in the cultivation of various agricultural crops, including maize. Sensing is an important part of these techniques. In our experiment we compared two methods: measuring relative chlorophyll content and the method of determine the extractable chlorophylls. The experimental plant was maize (Zea mays L.) and the measurements were performed at an early development stage (V8) of three genotypes. Three levels of nitrogen (0; 80; 160 kg ha-1) were applied during the experiment. The relative chlorophyll content was measured by SPAD-502 (Minolta, Japan) and a handheld GreenSeeker (Trimble, USA) device. The extractable total chlorophyll content decreased in parallel with the increased nitrogen level. The obtained SPAD values were diversified furthermore the NDVI values have not been changed for the effect of different nitrogen fertilization. In the early stages of development of maize, these parameters need to be complemented with other measurements to provide reliable information about the crops nitrogen status.